Optimization of the Integrated Security System Based on Traditional Villages (Sipandu Beradat) In The Framework of Preventing Motor Vehicle Theft in the Jurisdiction of the West Denpasar Police Station - Kevin Mario Immanuel; Mompang.L.Panggabean; Rospita Adelina Siregar (Universitas Muhammadiyah Palu, 2025)
Bali, as a premier tourist destination, has led to a high population density in Denpasar, increasing the risk of criminal activities, particularly motor vehicle theft (curanmor) in the West Denpasar jurisdiction. Effective policing efforts, including the implementation of the Integrated Security System Based on Traditional Villages (Sipandu Beradat), are needed to address this issue. However, due to the persistently high number of curanmor cases in the past three years, it is necessary to study the implementation and factors influencing the optimization of Sipandu Beradat. This study employs theories of cooperation, the Sipandu Beradat concept, policing science, management theory, crime prevention theory, and optimization concepts. The research is conducted using a qualitative method with a descriptive-analytical approach, involving interviews, observations, and document studies. Data analysis techniques include data reduction and data triangulation. The findings indicate that the Sipandu Beradat Forum has undertaken several efforts to prevent motor vehicle theft, such as joint patrols, socialization, inter-element communication, and regulation of incoming residents. However, these efforts have not been maximized due to several internal factors, including the lack of government-allocated funding and human resource constraints, as well as external factors such as environmental conditions and public vigilance. To optimize these efforts, it is necessary to secure funding, enhance personnel quality, and organize tasks and responsibilities more effectively. The conclusion of this study.